1999
DOI: 10.1159/000011993
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-Based Chemotherapy of Primary Extragonadal Germ Cell Tumours: The Hellenic Cooperative Oncology Group Experience

Abstract: Extragonadal germ cell tumours (EGCT) are uncommon, most frequently arise in the mediastinum and retroperitoneum and have variable responses to platinum-based chemotherapy. A retrospective analysis was performed on 38 patients with EGCT treated with cisplatin-based (CDDP) or carboplatin-based (CBDCA) chemotherapy between 1984 and 1998. Twenty-four patients had nonseminomatous germ cell tumours (NSGCT) and 14 seminoma. Twenty-two tumours arose in the mediastinum (13 nonseminomas, 9 seminomas) and 16 in the retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The outcome of malignant GCTs was poor, compared with that of mature teratoma, and nonseminomas had the worst prognosis. Cisplatin-based chemotherapy has recently been shown to improve survival in malignant GCTs [5,9,12,13]. However, both of the deaths in our study occurred in patients who had received chemotherapy.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The outcome of malignant GCTs was poor, compared with that of mature teratoma, and nonseminomas had the worst prognosis. Cisplatin-based chemotherapy has recently been shown to improve survival in malignant GCTs [5,9,12,13]. However, both of the deaths in our study occurred in patients who had received chemotherapy.…”
Section: Discussionmentioning
confidence: 65%
“…Though the outcome of mature teratoma seems good after surgical intervention, the prognosis of malignant GCTs in the mediastinum is not fully understood, especially that of nonseminomas [9][10][11]. The situation has shown some improvement since the introduction of platinum-based and high-dose chemotherapy [12][13][14]. However, the outcome is still poor and there is little data concerning Asian populations.…”
mentioning
confidence: 99%
“…Since 1970, the standard medical treatment in PMS is 4 to 6 cycles of chemotherapy with Cisplatin [16,21,22] or PVB. Tumor evaluation after chemotherapy in most cases reports remission of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that patients with primary extragonadal GCTs respond well to cisplatin-based combination chemotherapy, regardless of the site at presentation. 19 For this reason, the combination of chemotherapy and surgery is the most appropriate treatment strategy.…”
Section: Discussionmentioning
confidence: 99%